SYNTHESIS OF ACETAMIDOSULFONAMIDE DERIVATIVES WITH ANTIOXIDATIVE AND QSAR STUDIES - Apilak Worachartcheewan (2022)
A series of sixteen acetamidosulfonamide derivatives (1-16) have been synthesized and investigated for their antioxidant (radical scavenging and superoxide dismutase (SOD)) and antimicrobial activities. Most compounds exhibited antioxidant activities in which compound 15 displayed the most potent radical scavenging and SOD activities. Quantitative structure-activity relationship (QSAR) has been studied using multiple linear regression. 2 The constructed QSAR models displayed high correlation coefficient (QLOO- = 0.9708 and 0.8753 for RSA CV and SOD activities, respectively), but low root mean square error (RMSELOO-CV = 0.5105 and 1.3571 for RSA and SOD activities, respectively). The structure-activity relationship showed that an ethylene group connected to pyridine ring provided significant antioxidant activities. The QSAR models give insight into the rational designed of eighty new sulfonamides with various electron donating and withdrawing groups. The top five new designed sulfonamides with nitro group are potential antioxidants to be further developed for medicinal applications.